2017
DOI: 10.1007/s00216-017-0313-y
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected differences between planar and column liquid chromatographic retention of 1-acenaphthenol enantiomers controlled by supramolecular interactions involving β-cyclodextrin at subambient temperatures

Abstract: We report the results of experimental work focusing on host-guest supramolecular complex creation between macrocyclic compound (β-cyclodextrin) and 1-acenaphthenol enantiomers (racemic mixture) in liquid phase composed of 35% acetonitrile in water (v/v) at different temperatures ranging from 0 to 90 °C. Experimental setup involved several analytical protocols based on classical non-forced flow planar chromatography (RP-18 TLC plates), micro-TLC (RP-18 W HPTLC plates), column chromatography (HPLC with C-18 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
(68 reference statements)
0
13
1
Order By: Relevance
“…This part of the research reports a new analytical protocol enabling the rapid separation of eleven bisphenols using temperature-dependent inclusion chromatography (based on HPLC system) involving mobile phases modified with natural and biodegradable biomaterials: cyclodextrins. The separation process was performed on a typical octadecylsilane (low carbon load C18) analytical column [24,25]. In particular, the retention of supramolecular host-guest complexes occurring between native β-cyclodextrin (β-CD) or its highly soluble in water (and water/organic liquids) hydroxypropyl derivative (2-HP-β-CD) and target compounds, namely: bisphenol A, B, BP, Z, AF, AP, C, E, F, FL and S, was analyzed (Figure S1; Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This part of the research reports a new analytical protocol enabling the rapid separation of eleven bisphenols using temperature-dependent inclusion chromatography (based on HPLC system) involving mobile phases modified with natural and biodegradable biomaterials: cyclodextrins. The separation process was performed on a typical octadecylsilane (low carbon load C18) analytical column [24,25]. In particular, the retention of supramolecular host-guest complexes occurring between native β-cyclodextrin (β-CD) or its highly soluble in water (and water/organic liquids) hydroxypropyl derivative (2-HP-β-CD) and target compounds, namely: bisphenol A, B, BP, Z, AF, AP, C, E, F, FL and S, was analyzed (Figure S1; Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Optimization of column chromatographic separation of bisphenols standards and real samples was conducted using hardware setup described previously for selected naphthalene derivatives [25]. Basically, we used a chromatographic system where column temperature was controlled by foam insulated water jacket connected to circulating thermostat (Nestlab RTE7; product of Thermo Electron Corporation, Newington, NH, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the formation of inclusion complexes based on CDs was extremely sensitive to temperature and to competitive complexation with other small-molecule compounds (and their derivatives) found in biological systems (e.g., n -alkanes), although the reported impact of temperature on the stability of the generated complexes varies greatly among studies. While some studies have found that the formation of more stable complexes can be facilitated under lower temperature conditions [ 21 , 22 , 23 ], a high-temperature and high-pressure environment has also been reported in the literature as being able to facilitate the complexation process [ 24 ]. Such a discrepancy may have resulted from the variations in the mechanisms of different complexation processes.…”
Section: Resultsmentioning
confidence: 99%
“…Introducing PAHs (Fig. 2) as the sample probes, a systematic analysis of the interaction between the bonded stationary phase ligand(s) and the analyte could be carried out, because of these relatively simple molecular structures than real analytes to be separated in actual LC applications [36][37][38][39][40][41][42].…”
Section: )mentioning
confidence: 99%